Emerging Countries Taking on The World: The BRICS - Ahmed ALOUANI (Communications of International Proceedings, 2022)
Over the past thirty years, the Western world has witnessed the rise of previously underdeveloped countries, which have established themselves as major players on the world economic scene. Brazil, Russia, India, China, joined since December 2010 by South Africa within the “BRICS” group, are among the most prominent of them. The objective of this work is to see: what is the exact weight of the BRICS in the new world economy? Can we consider the BRICS as an economic pole?
Keywords: BRICS; Emerging; Challenges of competition; disoriented; who govners; vulnerable; economic pole.